CD4+ T cells in atherosclerosis: Regulation by platelets - Li, Nailin (Thrombosis and Haemostasis, 2013)
Atherosclerosis is an inflammatory and thrombotic disease, in which both CD4+ T cells and platelets play important roles throughout all stages of atherogenesis. CD4+ T cells are the most abundant T cells present in atherosclerotic lesions. They are primarily seen as type 1 T helper (Th1) cells, while the other CD4+ T cell subsets Th2, Th17, and regulatory T (Treg) cells are also found in the lesions with lower frequencies. CD4+ T effector cells release various cytokines, which exert paracrine or autocrine effects among different CD4+ T cell subsets and other lesional cells and subsequently modulate inflammatory processes in the lesions. Platelets are instrumental in thrombosis and haemostasis, but also play important regulatory roles in immune response, inflammation, and angiogenesis. The present review summarises the current knowledge and/or understanding on how platelets regulate recruitment, activation, differentiation, and cytokine production of different CD4+ T cell subsets, as well as impacts of the platelet-CD4+ T cell interactions on atherogenesis. The research perspectives of platelet-CD4+ T cell interaction in atherosclerosis are also discussed.
Keywords: Atherosclerosis; platelets; CD4+ T cells; chemokines; cytokines